Use of vault drainage for reducing vault haematoma during vaginal hysterectomy (Bangladesh Medical Journal, 2017)
A hysterectomy may be performed via abdominal, vaginal, or laparoscopic-assisted abdominal or vaginal approaches. Vaginal hysterectomy is associated with lower morbidity, faster recovery and shorter hospital stay compared with abdominal hysterectomy and should be considered the First choice for all benign conditions. But it is associated with a signi_cant risk of vault haematomas. Considering all the measures taken to reduce haematoma formation, vault drainage may help to reduce the postoperative complications and morbidity. The role of drain in abdominal surgery is well recognised. However, no formal evaluation of routine drain insertion at vaginal hysterectomy has been performed. This randomized controlled trial was conducted in the department of Obstetrics and Gynaecology, Dhaka Medical College & Hospital from January 2015 to June 2015 to find the result of vault drainage versus no drainage following vaginal hysterectomy. A total of 60 women scheduled for vaginal hysterectomy (30 cases for vault drainage and 30 cases for no vault drainage) during the study period were selected consecutively for the study. There was no significant difference between vault drainage group and no vault drainage group regarding age distribution, preoperative clinical history and vital parameters. The vault hematoma and febrile morbidity was significantly higher in no drainage group (Group I) than vault drainage group (Group II). No drainage group had significantly more duration of hospital stay than drainage group. This study showed that vault drainage during vaginal hypstrectomy is a safe and well tolerated technique and reduces vault hematoma.Bangladesh Med J. 2016 Sep; 45 (3): 121-125